The Effectiveness of Blooket.com; as an Evaluation Media for Arabic Vocabulary Learning: Efektivitas Blooket.com Sebagai Media Evaluasi Pembelajaran Kosakata Bahasa Arab - Labibah, Fitria Salwa Labibah; Erma Febriani; Agung Setiyawan (Hasanuddin University, 2024)
Blooket.com, the latest education-based game as a form of the development of learning innovations in the 4.0 Era that allows students to collaborate creatively to avoid monotonous learning. This study aims to determine the effective percentage of the use of Blooket.com as an evaluation medium for learning Arabic vocabulary. The research method used is Experimental research with a Quantitative approach, through a True Experiment research design with the type of Posttest Only Control Group Design. The effectiveness results are based on the results of the parametric test, namely an independent sample t-test which has previously gone through a descriptive analysis, normality test, and homogeneity test as a condition for the test used by the researcher. The results show that Blooket.com is a very effective evaluation tool to help students review Arabic vocabulary learning. Based on the test results, the average score of the experimental class was higher than that of the control class, with an average score of 93.55 : 84.90. The results of the study were shown by the significance value known in the effectiveness test of 0.001 < 0.05 through the Independent Sample T test. This research is expected to be a reference for the relevance of Arabic language learning innovations.